Geomechanics of Marine Anchors - Aubeny, Charles, author (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
"This book provides a comprehensive guide for the analysis and design of anchor systems used for mooring offshore floating structures. Much of the experience is based on applications toward the offshore oil and gas industry, but the substantial potential for offshore renewable energy systems is addressed. The major types of anchors are described with respect to their basic design concept, advantages and limitations, appropriate framework for analysis, and observed performance. This book addresses all aspects of anchor behaviour related to anchor design including the installation performance, load capacity, deformation, and structural integrity of the anchor itself. Coverage is also provided of appurtenant components of anchor systems, in particular of anchor line/chain mechanics in the soil and water columns. Much of the material presented represents relatively new developments, including several new anchors which have been developed within the last decade, so the book will provide a useful compendium of information is largely scattered in journals and conference proceedings. This book is intended for engineers engaged in offshore geotechnics and marine engineers involved in mooring system and floating structure design. While the analytical methods presented in this text have a strong theoretical basis, the emphasis is on simplified computational formats accessible to design engineers."